2018
DOI: 10.1002/cam4.1798
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown long noncoding RNA nuclear paraspeckle assembly transcript 1 suppresses colorectal cancer through modulating miR‐193a‐3p/KRAS

Abstract: The nuclear paraspeckle assembly transcript 1 (abbreviated as NEAT1), a nuclear sufficient long noncoding RNA (abbreviated as lncRNA), has aroused a rising concern in recent years. As uncovered by reports, the increase in NEAT1 is related to the deteriorated prognosis of lung cancer, breast cancer, hepatocellular cancer, and colorectal cancer (abbreviated as CRC). Thus far, the mechanism of NEAT1 has not been elucidated by the existing researches. The impact of knockdown of both NEAT1 and its predicted downstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 62 publications
(87 reference statements)
0
31
0
Order By: Relevance
“…Additionally, it has been reported that the regulation of miRNAs mediated by lncRNAs is involved in tumorigenesis and progression. For instance, the lncRNA nuclear paraspeckle assembly transcript 1 acts as a miR-193a-3p sponge to modulate the miR-193a-3p/KRAS pathway in colorectal cancer (17); lncRNA prostate cancer associated transcript-1 can promote NSCLC progression through competitively binding miR-149-5p and regulating the miR-149-5p/LRIG2 axis (18). In addition, lncATB serves as a molecular sponge to suppress interactions between miR-200b and Kindlin-2 in esophageal squamous cell carcinoma (19).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been reported that the regulation of miRNAs mediated by lncRNAs is involved in tumorigenesis and progression. For instance, the lncRNA nuclear paraspeckle assembly transcript 1 acts as a miR-193a-3p sponge to modulate the miR-193a-3p/KRAS pathway in colorectal cancer (17); lncRNA prostate cancer associated transcript-1 can promote NSCLC progression through competitively binding miR-149-5p and regulating the miR-149-5p/LRIG2 axis (18). In addition, lncATB serves as a molecular sponge to suppress interactions between miR-200b and Kindlin-2 in esophageal squamous cell carcinoma (19).…”
Section: Introductionmentioning
confidence: 99%
“…NOVA1, a member of the NOVA family of neuron-specific RNA-binding proteins, is aberrantly downregulated in multiple human cancers and affects a variety of pathophysiological processes associated with carcinogenesis and cancer progression (50)(51)(52). The expression and roles of NEAT1 and roles have been studied in other human cancers (43)(44)(45)(46)(47)(48)(49). Herein, we identified a novel NEAT1-miR-592-NOVA1 pathway, and this pathway could serve crucial roles in the aggressiveness of thyroid cancer.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, NOVA1 was validated as a direct target of miR-592 in thyroid cancer cells, and NEAT1 was proposed to function as a ceRNA to modulate NOVA1 expression by sponging miR-592. Multiple studies reported that NEAT1 is expressed at high levels and exerts oncogenic roles in a variety of human cancers, including cervical cancer (43), nasopharyngeal carcinoma (44), breast cancer (45), non-small cell lung cancer (46), colorectal cancer (47,48), and oral squamous cell carcinoma (49). NEAT1 is also upregulated in thyroid cancer (35)(36)(37), and upregulation of NEAT1 is positively correlated with TNM stage and tumor size (35).…”
Section: Discussionmentioning
confidence: 99%
“…NEAT1 was identified as a sponge of miR‐193a‐3p. Zhu et al () pointed out that NEAT1 could target miR‐193a‐3p to regulate the proliferation, migration, and apoptosis of colorectal cancer in vitro and meditate tumor growth in vivo (Zhu et al, ). NEAT1 has been widely studied in many human malignancies.…”
Section: Discussionmentioning
confidence: 99%